Barile's clinical toxicology : principles and mechanisms - Barile, Frank A. (Boca Raton, FL : CRC Press, 2019)
Examines the complex interactions associated with clinical toxicological events as a result of therapeutic drug administration or chemical exposure. Special emphasis is placed on signs and symptoms of diseases and pathology caused by toxins and clinical drugs. Includes the source, pharmacological and toxicological mechanism of action, detection and identification in body fluids, and treatment of exposure. An overview of protocols for managing various toxic ingestions, and the antidotes and treatments associated with their pathology, are discussed. In addition, effect of toxins on a limited number of body systems and drug-induced adverse drug reactions are also covered.
Introduction to Basic Toxicological Principles. Introduction. Risk Assessment and Regulatory Toxicology. Therapeutic Monitoring of Adverse Drug Reactions. Classification. Exposure. Effects. Dose Response. Descriptive Animal Toxicity Tests. In Vitro Alternatives to Animal Toxicity. Toxicokinetics. Chemical and Drug Receptor Interactions. Toxic Exposure and Surveillance in the U.S.. Toxicogenomics. Toxicity of Therapeutic Agents. Sedative -- Hypnotics. Opiods and Derivatives. Sympathomimetircs. Hallucinogenic Agents. Anticholinerigic and Neuroleptic Drugs. Acetaminophen, Salicylates, Non-steroidal Anti-inflammatory Drugs. Steroids. Cardiovascular Toxicology. Antineoplastic agents. Vitamins. Herbal Remedies. Toxicity of Non-Therapeutic Agents. Alcohols and Aldhydes. Gases. Metals. Aliphatic and Aromatic Hydrocarbons. Insecticides. Herbicides. Rodenticides. Chemical Carcinogenesis and Mutagenesis. Reproductive and Developmental Toxicity. Radiation Toxicity. Chemical and Biological Threats to Public Safety
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed April 26, 2019)
Keywords: Clinical toxicology; Toxicology -- Standards; Toxicity testing; Clinical pharmacology -- Standards; Clinical toxicology; Toxicity testing